2021
DOI: 10.3390/v13010112
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcomes of SARS-CoV-2 Infection in Asymptomatic Pregnant Women

Abstract: Around two percent of asymptomatic women in labor test positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Spain. Families and care providers face childbirth with uncertainty. We determined if SARS-CoV-2 infection at delivery among asymptomatic mothers had different obstetric outcomes compared to negative patients. This was a multicenter prospective study based on universal antenatal screening for SARS-CoV-2 infection. A total of 42 hospitals tested women admitted for delivery using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 23 publications
3
33
1
2
Order By: Relevance
“…In this multicenter prospective study, we investigated the association between SARS-CoV-2 infections and obstetric and neonatal outcomes. We found out that pregnant women with a SARS-CoV-2 infection had more premature rupture of membranes, more preterm births and, therefore, their neonates had more NICU admissions, compared to the pregnant women who were not infected [ 5 , 15 ]. The higher risk of premature rupture of membranes (overall as well as preterm) observed in the infected cohort can be explained by the fact that infections in pregnancy may be associated with this condition by various mechanisms, such as the activation of inflammation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this multicenter prospective study, we investigated the association between SARS-CoV-2 infections and obstetric and neonatal outcomes. We found out that pregnant women with a SARS-CoV-2 infection had more premature rupture of membranes, more preterm births and, therefore, their neonates had more NICU admissions, compared to the pregnant women who were not infected [ 5 , 15 ]. The higher risk of premature rupture of membranes (overall as well as preterm) observed in the infected cohort can be explained by the fact that infections in pregnancy may be associated with this condition by various mechanisms, such as the activation of inflammation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most SARS-CoV-2-induced placental alterations need time to determine the related clinical outcome. Studies that focus only on active infection with RT-PCR-positive samples [ 19 21 , 23 25 ] may rule out chronic conditions (chronic inflammation or placental vascular malperfusion) that can lead to preterm labor. Furthermore, the use of serological testing alone and not systematically associated to molecular sampling [ 25 ], may lead to the underestimation of those asymptomatic conditions negative for antibodies but positive for RT-PCR at testing.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, pregnant women from certain ethnic communities are more vulnerable to particular underlying conditions due to various social disparities in healthcare, and subsequently, these groups' increased susceptibility to severe cases of SARS-CoV-2 infection should be taken into account for future studies. Furthermore, future research should investigate the possible role of variants of SARS-CoV-2 in vertical transmission from an infected mother to her fetus since this virus has evolved and mutated a significant number of times since its emergence in December 2019 (van Dorp et al, 2020 Baud et al, 2020;Dong et al, 2020;Pulinx et al, 2020;Vivanti et al, 2020b;Saccone et al, 2021 SARS-CoV-2 infection in lungs; Patchy or hazy opacities near or on lungs Dong et al, 2020;Wu C. et al, 2020;Xiong et al, 2020;Zhou et al, 2020;Zhu et al, 2020;Cruz-Lemini et al, 2021 SARS-CoV-2 infection in placenta; Intervillosis observed in placenta; Abnormalities in the placenta Baud et al, 2020;Fenizia et al, 2020;Hosier et al, 2020;Naz et al, 2020;Pulinx et al, 2020;Vivanti et al, 2020b;Zhou et al, 2020;Zhu et al, 2020 SARS-CoV-2 infection in umbilical cord; Abnormalities and/or inflammation of umbilical cord Baud et al, 2020;Fenizia et al, 2020;Hosier et al, 2020;Naz et al, 2020;Zhu et al, 2020 SARS-CoV-2 infection in maternal blood Fenizia et al, 2020;Pulinx et al, 2020;Vivanti et al, 2020b SARS-CoV-2 infection in amniotic fluid Fenizia et al, 2020;Pulinx et al, 2020;Vivanti et al, 2020b;Zamaniyan et al, 2020;Zhu et al, 2020 Mild to moderate (occasionally severe) COVID-19 disease symptoms in infected pregnant women…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2020;Xiong et al, 2020;Zamaniyan et al, 2020;Zhou et al, 2020;Zhu et al, 2020;Bellos et al, 2021;Di Toro et al, 2021;Saccone et al, 2021 Cytokine storm involved in immune response in infected pregnant women against SARS-CoV-2; Increased cytokine levels Dhama et al, 2020;Fenizia et al, 2020;Narang et al, 2020 Lymphopenia observed in infected pregnant women Areia and Mota-Pinto, 2020;Chen et al, 2020;Chi et al, 2020;Dhama et al, 2020;Hosier et al, 2020;Narang et al, 2020;Vivanti et al, 2020b;Wu C. et al, 2020;Wu Y.T. et al, 2020;Zamaniyan et al, 2020;Bellos et al, 2021;Cruz-Lemini et al, 2021;Di Toro et al, 2021;Saccone et al, 2021 Elevated C-reactive protein levels in SARS-CoV-2 infected pregnant women Areia and Mota-Pinto, 2020;Chen et al, 2020;Chi et al, 2020;Dhama et al, 2020;Pulinx et al, 2020;Vivanti et al, 2020b;Wu C. et al, 2020;Wu Y.T. et al, 2020;Zamaniyan et al, 2020;Bellos et al, 2021;Di Toro et al, 2021 Increased levels of anti-SARS-CoV-2 IgM and IgG antibodies in pregnant women Dong et al, 2020;Hosier et al, 2020;Iyer et al, 2020;Zhou et al, 2020 Elevated levels of D-dimer in SARS-CoV-2 infected pregnant women…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation